GnRH pulses--the regulators of human reproduction. - Marshall, J. C. (American Clinical and Climatological Association, 1993)
The data reviewed in this chapter provide evidence that the pattern of GnRH secretion appears to be an important factor in regulating gonadotropin subunit gene expression, gonadotropin synthesis and hormone secretion. The data on gonadotropin synthesis were obtained in rodents and hence, must be interpreted with caution when applied to primates. Despite this reservation, the data suggest a similarity of regulatory mechanisms in mammalian species. The data also provide an explanation for the mechanisms whereby a single gonadotropin-releasing hormone can differentially regulate the three gonadotropin genes and allow differential hormone secretion. In overall agreement with this view, the observations during pubertal maturation reveal increasing GnRH pulsatile secretion during puberty with an evolution from predominant FSH to a predominant LH secretion by the gonadotropes. In males, the patterns of GnRH secretion appear to be fairly consistent throughout adult life, but in women cyclic changes occur which perhaps are important in maintaining cyclic ovulation. It is proposed that once pubertal maturation has been established, GnRH is secreted at a relatively fast frequency (one pulse per hour), and an essential feature of repeated ovulatory cycles is the slowing of this GnRH stimulus during the luteal phase: to allow subsequent preferential FSH release. This slowing of GnRH secretion appears to be effected by estradiol and progesterone acting to enhance hypothalamic opioid activity. Similar mechanisms involving increased opioid tone appear to be causally related to the reduced frequency and irregular GnRH stimulus seen in hypothalamic amenorrhea and hyperprolactinemia. In contrast, some forms of polycystic ovarian disease may reflect abnormalities of the estradiol-progesterone/opioid/GnRH neuron feedback mechanisms, with failure to establish slowing in the peripubertal anovulatory cycles. The resulting persistent GnRH stimulus increases LH with consequent effects of abnormal follicular maturation and enhanced ovarian androgen production. Present data are supportive of these hypotheses, but future studies will determine whether these views prove to be correct. However, current data provide strong support for the view that the pattern of GnRH secretion is a critical factor in the regulation of differential gonadotropin synthesis and secretion in mammalian species.